Pengelolaan Keuangan Desa : Studi Pada Desa Ploso Kecamatan Jombang Tahun Anggaran 2012-2016: Village Financial Management: A Study in Ploso Village, Jombang District, 2012-2016 Fiscal Year - Andrianto, Andrianto (Journal of Accounting Science, 2018)
With the enactment of Law No. 6 of 2014 on villages, it is desirable that in the management of the village, especially in the management of its finances, it can be done accountably and responsibly. This study aims to identify the financial management of the village along with the problems associated with the management of village finances conducted in the Village Ploso Jombang. This research uses qualitative method with case study approach, where most of the research implementation mostly use observation and interview method. The results show that in the management of village finances there are main issues that is the lack of knowledge of village head and its officials in the management of budget and village finances. This research proposes the existence of computerized system accompanied by training and guidance of village financial management from local government apparatus, so it is expected that village financial reporting can be done by fast process and with output of accountable and accountable financial statement.